INTEGRASI KEWIRAUSAHAAN DALAM PENDIDIKAN TEKNOLOGI KEJURUAN: TANTANGAN DAN PELUANG - Permata Saputri, Renny; Harleni, Harleni; Jalinus, Nizwardi; Mardizal, Jonni (Ensiklopedia of Journal, 2024)
This study aims to analyze the integration of entrepreneurship within vocational technology education in Indonesia, focusing on current conditions, challenges, opportunities, effective integration models, and their impacts on graduates. The research employs a mixed-method approach, combining literature review, observation, and in-depth interviews with relevant stakeholders. The findings reveal that while most vocational technology institutions have incorporated entrepreneurship, the approaches remain predominantly theoretical and lack comprehensive integration. Key challenges include curriculum design, resource limitations, and stakeholder mindsets. On the other hand, opportunities arise from government policy support, industry collaboration, and digital technology-driven learning innovations. An effective entrepreneurship integration model requires a holistic curriculum, innovative teaching methods, strategic collaboration, resource management, and mindset transformation. Effective entrepreneurship integration positively impacts technical and entrepreneurial competencies, entrepreneurial motivation, adaptability, economic contributions, and graduates' career success.Keywords: entrepreneurship integration, vocational technology education, challenges, opportunities, integration model, graduate impact